Lifestyle and Epidemiology The Double Burden of Poverty and Cardiovascular Diseases in African Populations - Daniel Monyeki, Kotsedi; Kemper, Han C.G (IntechOpen, 2021)
Lifestyle and Epidemiology - The Double Burden of Poverty and Cardiovascular Diseases in African Populations examines the profile of non-communicable diseases (NCDs) in the rural South African population. The burden of diseases in South Africa is characterized by a combination of poverty-related diseases with emerging NCDs associated with urbanization, industrialization, and a Westernised lifestyle. Chapters in this book examine the effects of poverty, COVID-19, and other social factors on the prevalence of cardiovascular disease, reproductive health, and diabetes in rural South Africa.